International legal regulation and reflection on the protection of the rights and interests of cross-border tourists between China and Kazakhstan - Wang, Hong-wei; Liu, Wen-hao; Su, Ming-zhe (Karagandy University of the name of academician E.A. Buketov, 2025)
With the deepening of globalization and the effective control of the epidemic, cross-border tourism has grad ually become a common lifestyle. With the implementation of Kazakhstan’s visa-free policy for Chinese tour ists and the rapid development of China’s economy, tourism between China and Kazakhstan is becoming more frequent. However, both countries are emerging countries, and the legal protection mechanism for tour ists’ rights is still imperfect. The protection of the rights and interests of cross-border tourists has become a focus of attention. However, at the level of international cooperation, the protection of the rights and interests of cross-border tourists is still weak. Due to the local nature of knowledge, differences in legal systems in dif ferent countries, obstacles to judicial remedies, and imperfect dispute resolution mechanisms, the protection of the rights and interests of cross-border tourists faces great challenges. In view of this, it is of practical ur gency to promote in-depth cooperation between China and Kazakhstan in the field of rule of law from the perspective of international law and establish an effective cross-border tourism dispute resolution mechanism.
Keywords: International law; legislations; dispute; resolution mechanism; cross-border passengers; cross border tourism; passenger rights; China